Cloud computing as a platform for genomic data analysis and collaboration - Langmead, Ben (Nat Rev Genet, 2018)
DNA sequencing made huge strides in the last decade. Studies based on large sequencing datasets appear frequently, and public archives for raw sequencing data have been doubling in size every 18 months. Meanwhile, commercial and academic cloud computing have matured, leading to more providers, greater total capacity, and a larger variety of services. Here we describe how cloud computing is used for large-scale genomics collaborations and research and argue how cloud computing will likely be a basic underpinning for future large-scale genomics collaborations and for efforts to re-analyze archived data, including privacy-protected data.